2005
DOI: 10.1002/mnfr.200500014
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antigenotoxic effects of plant cell wall hydroxycinnamic acids in cultured HT‐29 cells

Abstract: We demonstrate that two hydroxycinnamic acids, (E )-ferulic acid and (E )-p-coumaric acid, have the ability to protect against oxidative stress and genotoxicity in cultured mammalian cells. They also show the ability to reduce the activity of the xenobiotic metabolising enzyme, cytochrome P450 1A, and downregulate the expression of the cyclooxygenase-2 enzyme. At equitoxic doses, their activities are equal to or superior to that of the known anticarcinogen, curcumin. The hydroxycinnamic acids are both importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(149 citation statements)
references
References 42 publications
2
137
1
9
Order By: Relevance
“…Among others, the comet assay has become one of the standard methods for assessing DNA integrity (Collins 2004 ). Ferguson et al ( 2005 ) demonstrated both in vitro antioxidant activity and antigenotoxic effect in HT29 cells by using a comet assay for two hydroxycinnamic acids with an important percentage in certain plant foods, as spinach or cereals. Interestingly, the protection of resveratrol and quercetin against exogenous pro-oxidative damage was determined in HT29 cells with induced oxidative stress by addition of fatty acid hydroperoxides (Kaindl et al 2008 ).…”
Section: Functionality Studiesmentioning
confidence: 99%
“…Among others, the comet assay has become one of the standard methods for assessing DNA integrity (Collins 2004 ). Ferguson et al ( 2005 ) demonstrated both in vitro antioxidant activity and antigenotoxic effect in HT29 cells by using a comet assay for two hydroxycinnamic acids with an important percentage in certain plant foods, as spinach or cereals. Interestingly, the protection of resveratrol and quercetin against exogenous pro-oxidative damage was determined in HT29 cells with induced oxidative stress by addition of fatty acid hydroperoxides (Kaindl et al 2008 ).…”
Section: Functionality Studiesmentioning
confidence: 99%
“…There are three isomers, o-coumaric, m-coumaric and p-coumaric acid, that diff er by the position of the hydroxy substitution of the phenyl group. p-Coumaric acid is the most abundant isomer in nature, has antioxidant properties 55 and is believed to reduce the risk of stomach cancer 56 .…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Also, p-coumaric acid is abundantly present in pineapple. It has been found to reduce the risk of stomach cancer [5] by reducing the formation of carcinogenic nitrosamines [6]. Based on the above literature data only few studies have been carried out for PCA molecule.…”
Section: Introductionmentioning
confidence: 99%